Think Before You Post: Cerdas Berkomunikasi Di Era Digital - Arief A.S; Fahmi Alhadi; Nawaf Alhadi; Sofia Nugraheni; Sela Denita; Nova Fitri; Ocha Shelvia; Juraida; Widia Rahmasia; Afnizah; Iwan Doa Sempena (Jurnal Riset Multidisiplin Edukasi, 2026)
In the digital era, social media has become a communication tool used by various segments of society. The ease of disseminating information requires internet users to be more prudent in using social media. This journal discusses the importance of the "think before you post" principle as a form of smart and responsible communication in the digital age. The purpose of this paper is to raise public awareness about thinking critically before sharing information or comments on the internet. The method used is a literature study, gathering information from various sources related to digital communication ethics. The results of the discussion show that being wise on social media can help reduce the spread of hoaxes, hate speech, and privacy violations. Therefore, implementing the "think before you post" principle is crucial to creating a digital environment that is safe, positive, and comfortable for all users."